Efecto del ganado sobre la estructura de la vegetación en las riberas de un arroyo pampeano - Gantes, P. (2014)
Livestock is a main perturbation for the riparian zones of streams in the Buenos Aires province. Our goal is to compare the vegetation’s and soil’s characteristics of two almost contiguous reaches of the Nutrias stream, an affluent to the Reconquista river. One reach has been closed to cattle for 2 years, and the other -500m downstream- has kept livestock along the whole period. For each stream margin, six 10m transects were sampled for species cover and 3 soil samples were drawn for organic matter, phosphorus, pH, conductivity and apparent density determination. The vegetation’s canopy hight, cover, and the amphibious macrophytes’ abundance were higher in the closed reach; instead, species number was higher in the reach opened to cattle. Eleocharis bonariensis (19%), Paspalum distichum (17%) y Cynodon dactylon (15%) were dominant within the closure, while the exotic grass C. dactylon dominated (63%) in the grazed reach. Regarding the soil variables, a PCA distinguishes the two reaches in the first component (35% of the total variance), and the two margins of the closed reach are separated along the 2nd axis (25%). This separation of the reaches and the margins is consistent with the ordination analysis (NMDS) performed among the species. In this case study, the observed changes in the community structure after two years of closure may enhance the riparian zone’s capability to regulate the exchanges between land and watercourse.